Shadow Creek : a novel - Fielding, Joy (Emily Bestler Books/Atria, 2012)
An unlikely group of campers including a woman, her two oddball friends, her teen daughter and her ex's fiancé embark on a trip in the Adirondacks only to be targeted by a pair of teenage killers.